The causal relationship between infant mortality rate, health expenditure and economic growth in India - Sharankumar Holyachi,; Prakash R. Kengnal, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction The Infant Mortality Rate defined as the risk for a live born child to die before its first birthday, is known to be one of the most sensitive and commonly used indicators of the social and economic development of a nation. This paper investigates the causal relationship between infant mortality rate, economic growth and private health expenditure [% Gross Domestic Product (GDP)] in India using the co-integration and Granger causality frameworks for the period from 1995 to 2013 using secondary data from various sources. Methods We have examined the presence of a long-run equilibrium relationship using the bounds testing approach to co-integration within the Unrestricted Error- Correction Model (UECM). We have also examined the direction of causality between infant mortality rate, economic growth and private health expenditure (% GDP) in India using the Granger causality test within the Vector Error-Correction Model (VECM). Results and Conclusions As a summary of the empirical findings, we find the Infant Mortality Rate (IMR), Per-Capita Gross Domestic Product (PCGDP) and private health expenditure (% GDP) are co-integrated. The results of Granger Causality suggested that no short-run effect was existing between all the three variables. The error-correction term implies that the variable is non-explosive and long-run equilibrium relationship is attainable.